The role of holistic mentoring ecosystems in mitigating COVID-19 pandemic impacts on the persistence of low-income STEM students - Davis, Raeshan D.; Wilson-Kennedy, Zakiya S. (Frontiers in Education, 2024)
Holistic mentoring ecosystems are a comprehensive approach to addressing the diverse needs of students through interconnected support networks. While mentoring has been well-documented in existing literature, more research is needed to determine the effectiveness of mentoring ecosystems in mitigating the impact of critical junctures for vulnerable, high-attrition student populations. Guided by Tinto’s model of retention, this qualitative case study investigated the role of holistic mentoring ecosystems in mitigating the impacts of the two combined critical junctures—the COVID-19 pandemic and the first year of college—on low-income STEM undergraduates. Our findings suggest that holistic mentoring ecosystems were essential in helping students adjust to the academic environment and fostering a sense of belonging in the STEM community amid the severe limitations imposed by the pandemic. This study adds to the growing body of literature investigating the approaches and strategies effective in supporting vulnerable student populations through critical junctures in their educational journey.